Colonization and infection in the newborn infant: Does chlorhexidine play a role in infection prevention (2017)
Healthcare-Associated infections are a major problem in newborn infants, considering their high morbidity, mortality, and long-Term sequelae. In preterm infants, it has been shown that skin and gastrointestinal tract colonization undergoes variations compared to healthy term infants, and that preterm infants are more exposed to nosocomial microorganisms given their higher probability of being admitted to the neonatal intensive care unit where they are cared for. This document reviews normal colonization, the changes observed during hospitalization, prematurity, and the potential role of chlorhexidine in the prevention of resistant microorganism transmission, as well as its side effects in newborn infants admitted to the neonatal intensive care unit.